Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Konsumen pada Supermarket Super Indo Kenjeran Surabaya - Rahmat Pratama; Iswati Iswati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the era of globalization and advances in information technology, business competition in various sectors is getting tighter, including in retail industries such as supermarkets. Supermarkets are not only a place to meet daily needs, but also become part of the busy lifestyle of urban people. In this context, the quality of services and products offered by a supermarket has a very important role in maintaining and increasing market share and customer satisfaction. The survey was conducted both directly in the Super Indo Kenjeran Supermarket area and online through an online survey platform. The survey design used is a cross-sectional survey, where data is collected at one particular point in time to measure the relationship between the variables studied. In this context, research on the effect of service quality and product quality on customer satisfaction at PT. Lion Super Indo Kenjeran becomes relevant and important to do. With a better understanding of the factors that affect customer satisfaction, PT. Lion Super Indo Kenjeran can identify areas that need improvement and design more effective strategies in maintaining and increasing customer loyalty. Lion Super Indo as one of the leading supermarkets in Indonesia, with a long history and strong reputation, certainly does not escape from increasingly fierce business competition. Therefore, a deep understanding of the factors that affect customer satisfaction is a strategic key in maintaining the existence and developing the business of PT. Lion Super Indo.